OPTIMALISASI LAYANAN PENGADAAN SECARA ELEKTRONIK DI POLDA SUMBAR GUNA MENCAPAI PRINSIP PENGADAAN DALAM RANGKA TERWUJUDNYA KEPERCAYAAN MASYARAKAT - Supriadi M (Ensiklopedia of Journal, 2021)
Presidential Regulation of the Republic of Indonesia Number 16 of 2018 concerning Government Procurement of Goods / Services, and which reads in article 6 explains that the principles of implementing goods / services procurement are carried out efficiently, effectively, transparently, openly, competitively, fairly and accountably. So to implement this, the procurement of goods / services using APBN, Provincial APBD, or District / City APBD will carry out auctions with Electronic Auction Services (LPSE). One of them is the Electronic Auction Service (LPSE) which is also applied to the West Sumatra Police. However, the implementation of this system has not run optimally. This is partly due to the condition of Human Resources (HR) and budget conditions on Electronic Procurement Services (LPSE) at Polda West Sumatra. From the results of the review and identification, it was found that the cause of the inadequate implementation of the Electronic Auction Service (LPSE) in the West Sumatra Regional Police in terms of Human Resources (HR) aspects, including the lack of personnel availability in e-procurement procurement and the low level of personnel capabilities, while from the budget aspect including the absence of a budget for honorarium, training budget and budget for maintenance of Electronic Procurement Service (LPSE) inventory items.